Marco para el análisis de la seguridad social en el perú - Sanabria Montañez, César A. (2008)
The present article is an advance of the study that develop in the Institute of Economic Investigations of the National University Main of Saint Marcos, pretends to be a frame of reference of the study on social security, thus it explores the economic context social Peruvian, to the light of the existent contradiction between economic growth and poverty; likewise examines the main characteristics of the employment, the demographical growth and the future the future changes for the society in terms of investment in the people through the social security; review also the state of the art of the social security in health and of pensions in the Peru. Finally presents the conceptual frame of what understand by social security from the economic approach.